Keefektifan Konseling Keluarga dalam Memperbaiki Skor Ekspresi Emosi pada Caregiver Pasien Skizofrenia - Badriyah, Siti (Jurnal Kedokteran Indonesia, 2011)
Background: Families with a schizophrenic member often experience over-expression of recurrentemotion that may cause the schizophrenic member to relapse. Alleviating this emotion expressioncan help schizophrenic patients to attain better prognosis, improve their social function, and enhancetheir quality of life. Eclectic family counseling is a type of psycho-social therapy that helps familymembers to actualize their potentials, to anticipate problems within family system, and to inducepositive behavioral change to other family member. This study aimed to determine the effectivenessof family counseling in improving emotional expression score of the caregivers of patients withschizophrena.Methods: A double-blinded randomized controlled trial was conducted at the Municipal Mental Hospital(RSJ) Surakarta from February to March 2011. A sample 40 patients with schizophrenia and 40 familymembers (caregivers) of these patients was selected by purposive sampling. These caregivers were20 to 50 years of age, either male or female, and livedwith the patients at least 8 hours per day in thesame houses. The caregivers were assigned at random into the experimental group (n1= 20) whoreceived family counseling and the control group (n2= 20) who did not receive family counseling. Theoutcome variables under study were Emotional Over-Involvement (EOI) and Critical Comments (CC)of the caregivers, as well as the quality of life (QoL), and personal and social performace (PSP) of theschizophrenic patients, using validated scales. Multiple linear regression analysis was run to measurethe effect of the counseling on these outcome variables.Results: Caregivers that received family counseling showed decline in EOI (b= -4.69; 95%CI -6.12 to -3.28), and (CC)(b= -3.75; 95%CI -5.24 to -2.37). Schizophrenia patients who received care from caregiverwith counseling showed improvement in QoL (b= 17.71; 95 %CI 11.89 to 23.54), and PSP (b= 19.05; 95%CI15.20 to 22.92).Conclusion: Eclectic family counseling effectively reduces excessive emotional expression among familycaregivers with a schizophrenic patient, thereby improves the quality of life as well as personal andsocial performance of the patient.Keywords: family counseling, emotional expression, quality of life, personal and social performance